Turnover Intention in Relation to Job Stress and Workload Among Male and Female Employees at PT. Matahari Department Store Tbk, Medan - Anggi Derissa Putri Sianturi; Lamtiur Melinda; Yosephine Deborah Situmorang; Kharine Tiatira Sirait; Sri Hartini (TALENTA Publisher, Universitas Sumatera Utara, 2025)
This study explores the relationship between job stress, workload, and turnoverintention among male and female employees at PT. Matahari Department StoreTbk, Medan. Using a quantitative approach, data were collected from 133employees through validated questionnaires measuring turnover intention, jobstress, and workload. The study employed multiple linear regression analysisusing SPSS Statistics 25 to examine the influence of the independent variables.The findings reveal that both job stress and workload significantly affectemployees' turnover intention. Job stress has a positive and significant effect witha beta coefficient of 0.511 (p = 0.000), while workload also shows a significantpositive effect with a beta coefficient of 0.473 (p = 0.000). The regression modeldemonstrates a strong explanatory power, with an adjusted R² value of 0.941,indicating that 94% of the variance in turnover intention is explained by job stressand workload. The remaining 6% is attributed to other unmeasured factors. Theseresults underscore the need for organizations to address workplace stressors andmanage workloads effectively to reduce employee turnover, especially whenconsidering gender-related experiences in the work environment